DETERMINANTS OF PRODUCTION AND TECHNICAL EFFICIENCY IN THE SIWALAN SUGAR BUSINESS IN KARDULUK VILLAGE - Dwi Wahyu; Norita Vibriyanto (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2026)
Despite the economic importance of siwalan sugar for rural livelihoods, studies integrating production determinants and technical efficiency analysis using the stochastic frontier approach remain limited. This study aims to analyse the effects of labour, nira volume, and business capital on siwalan sugar production and to measure the technical efficiency of producers in Karduluk Village, Pragaan Subdistrict, Sumenep Regency. This study employs a quantitative approach using primary data obtained from 101 siwalan sugar producers selected through purposive sampling. The analysis was conducted using Stochastic Frontier Analysis (SFA) approach. The results of the study indicate that the labor force, sap volume, and business capital have a positive and significant effect on siwalan sugar production, suggesting that an increase in the number of workers, sap volume, and business capital is associated with an increase in siwalan sugar production. The average technical efficiency score was 0.9625, indicating that producers operated close to the estimated production frontier, although output could still increase by approximately 3.8 percent through more efficient utilization of existing inputs. These findings imply that policies should prioritize strengthening raw material management through better utilization of untapped siwalan resources while simultaneously improving production technology and institutional support, including extension services, producer organizations, and market access for small-scale siwalan sugar producers.   Meskipun gula siwalan memiliki peran ekonomi yang penting bagi mata pencaharian masyarakat pedesaan, penelitian yang mengintegrasikan analisis faktor-faktor penentu produksi dan efisiensi teknis dengan menggunakan pendekatan stochastic frontier masih terbatas. Penelitian ini bertujuan menganalisis pengaruh tenaga kerja, volume nira, dan modal usaha terhadap produksi gula siwalan serta mengukur efisiensi teknis para produsen di Desa Karduluk, Kabupaten Sumenep. Penelitian ini menggunakan pendekatan kuantitatif dengan memanfaatkan data primer dari 101 produsen gula siwalan yang dipilih melalui metode purposive sampling. Analisis menggunakan pendekatan Stochastic Frontier Analysis (SFA). Hasil penelitian menunjukkan bahwa tenaga kerja, volume nira, dan modal usaha berpengaruh signifikan terhadap produksi gula siwalan. Hal ini menunjukkan bahwa peningkatan jumlah tenaga kerja, volume nira, dan modal usaha berkaitan dengan peningkatan produksi gula siwalan. Nilai rata-rata efisiensi teknis yang diperoleh sebesar 0,962, yang mengindikasikan bahwa produsen telah beroperasi mendekati batas produksi (production frontier) yang diperkirakan, meskipun output masih dapat ditingkatkan sekitar 3,8 persen melalui pemanfaatan input yang tersedia secara lebih efisien. Temuan ini menunjukkan kebijakan perlu memprioritaskan penguatan pengelolaan bahan baku melalui pemanfaatan sumber daya siwalan yang belum optimal, sekaligus meningkatkan teknologi produksi dan dukungan kelembagaan, termasuk layanan penyuluhan, organisasi produsen, serta akses pasar bagi produsen.